THE EFFECTIVENESS OF MICROSURGICAL VARICOCELECTOMY IN TREATING MALE INFERTILITY AT 19-8 HOSPITAL, MINISTRY OF PUBLIC SECURITY (Vietnam Journal of Community Medicine, 2022)
Introduction and objectives: Varicocele is among the most common causes of maleinfertility. Our study aimed to evaluate the effectiveness of microsurgical varicocelectomyin treating male infertility.Subjects and methods: Data were collected prospectively from 55 cases of infertile menwith clinical varicocele who underwent microsurgical varicocelectomy from Dec 2018 toDec 2021 at the Department of Urology, 19-8 Hospital, Ministry of Public Security. Patientswere followed-up 3, 6 and 9 months using semen analysis and hormonal tests.Results: Mean age of patients was 29,09 ± 2,72 years. Primary infertility was found in 83,64%of patients and the prevalence of secondary infertility was 16,36%. Symptom improvementhas been reported in most of patients after the surgical. The sperm analysis revealedstatistically significant increases in sperm concentration, progressive sperm motility andnormal morphology (p
Keywords: Varicocele, microsurgical varicocelectomy, semen analysis, testosterone, male infertility.